SARS-CoV-2 Prevalence on and Incidence after Arrival in Travelers on Direct Flights from Cape Town, South Africa to Munich, Germany Shortly after Occurrence of the Omicron Variant in November/December 2021: Results from the OMTRAIR Study - Cornelia Seidl; Liza Coyer; Nikolaus Ackermann; Katharina Katz; Jan Walter; Siegfried Ippisch; Martin Hoch; Merle M. Böhmer (Pathogens, 2023)
The highly transmissible SARS-CoV-2-variant B.1.1.529 (Omicron) first appeared in South Africa in November 2021. In order to study Omicron entry to Germany, its occurrence related to incoming airline travel, symptomatology and compliance with entry regulations and recommendations, we conducted a cross-sectional study, followed by a retrospective cohort study among passengers and crew on 19 direct flights from Cape Town, South Africa, to Munich, Germany, between 26 November and 23 December 2021. Travelers were mandatorily PCR-tested on arrival and invited to complete an online questionnaire. SARS-CoV-2-prevalence on arrival was 3.3% (n = 90/2728), and 93% were Omicron. Of the passengers, 528 (19%) completed the questionnaire. Among participants who tested negative on arrival, self-reported SARS-CoV-2-incidence was 4.3% within 14 days, of whom 74% reported a negative PCR-test ≤ 48 h before boarding, 77% were fully vaccinated, and 90% reported wearing an FFP2/medical mask during flight. We found multiple associations between risk factors and infection on and after arrival, among which having a positive-tested travel partner was the most noteworthy. In conclusion, PCR testing before departure was insufficient to control the introduction of the Omicron variant. Additional measures (e.g., frequent testing, quarantine after arrival or travel ban) should be considered to delay virus introduction in such settings.